Challenges and Opportunities of Using School Readiness Screening Tool for Learners with Special Needs in Kenya - Wanyera, Samuel (JOOUST, 2015)
The School Readiness Screening test Tool is important because it is used by Educational Assessment Resource and Research Centres, to determine school placement and intervention strategies for learners with Special Needs to join Pre-school programme in Kenya. The tool has been in use since in the Centres in Kenya since 1984 and yet its efficacy is still in doubt. The purpose of this study was to find out the Challenges and Opportunities of using School Readiness Screening Tool for Learners with Special Needs in Kenya. The specific objectives of this study were to: Determine difficulties in use of school Readiness Screening Tool adopted for early Intervention and school placement; Suggest additional test content that can be incorporated in School Readiness Screening Tool to give opportunity to screen contemporary categories of learners with Special Needs and Disabilities. This study adopted a concurrent triangulation design. Qualitative data were presented in narrative form, while quantitative data were analysed using frequency counts, percentages, mean scores, and spearman rank correlation coefficient. The target population was 32 Educational Assessment Professionals working in the eight regional centres of Kenya covering all the counties of Kenya. Purposive sampling was used to sample twenty-five Educational Assessment professionals who are the coordinators of the Centres from City, Urban, Rural and Semi-arid settings. lnstruments used to collect were interview schedule, observation schedule, focus group discussion guide and document analysis guide. Reliability of the instruments was established by pre-testing them in three of the assessment centres with City, Rural, Urban and Semi-arid settings where the study was carried out. Validity of the instruments was established through vetting by the two University supervisors and one Professional from Educational Assessment Resource and Research Centre. The findings revealed that screening using School Readiness Screening does not screen all the categories of learners with Special Needs and disabilities. Sixty eight percent of the Education Assessment Professionals said additional Test content to the Tool could give opportunity for screening Learners with Special Needs and Disabilities. Other challenges included use of Mother Tongue language during screening process, and lack of validated Tool to Screen all learners in the Centres in Kenya. Pearson product moment correlation coefficient analysis, the results showed that there was no significant relationship in the training levels of the respondents to the use of school readiness screening tool (r = 0.866, P = 0.333). From the study findings the respondents suggested additional test content, and developmental Check Lists for different categories of Special Needs Learners being screened. The study recommended that the Ministry of Education through Quality Assurance Standards, Kenya Institute of Curriculum Development should involve all the stakeholders in validation of the Screening Tool.